Nickel(II) Complexes of ONS and ONN Chelating Thiosemicarbazones With Triphenylphosphine Co-Ligands - Güveli, Ş.; Bal-Demirci, T.; Özdemir, Nutullah; Ülküseven, B. (Springer, 2009)
Reactions of 5-bromo-2-hydroxy-benzaldehyde-S-R-4-R1- thiosemicarbazones, [R, R1 = H,H (L1); CH3, H (L2); H, C6H5 (L3); CH3, C6H5 (L4)] with [Ni(PPh3) 2Cl2] in 1:1 molar ratio yielded complexes of general formula [Ni(L)(PPh3)]. While the complexes of L1 and L3 involve the ONS donor set of the thiosemicarbazone, the L 2 complexes utilize the ONN set. The reaction of L4 and the nickel salt gave the L3 complex by loss of the CH3 group from the sulphur. The complexes were characterized by physico-chemical and spectroscopic methods. The structures of the L1 and L2 complexes have been determined by single crystal X-ray diffraction and a new coordination mode (ONN) of salicylaldehyde thiosemicarbazones has been identified. © 2009 Springer Science+Business Media B.V.